The metamorphosis of eLearning - Elspeth McKay (Flexible Learning Association of New Zealand, 2012)
The scope of eLearning is more comprehensive than the commonly accepted issue of technological instructional/learning materials. Confusion abounds. Which voice is believable? Is there any common ground? This paper illustrates how wise use of the technologies can provide the leverage human beings require for expanding their horizons for lifelong learning.